Teori Pembelajaran dan Dampaknya pada Pengembangan Kurikulum di SMAN 3 Bukittinggi - Lestari, Kurnia Mira; M, Iswantir; Gusli, Ramadhoni Aulia (Program Studi Magister Pendidikan Agama Islam, 2024)
Transformation, which is a change in behaviour, is an indication that a person is learning. Students experience three domains of education: cognitive, affective, and psychomotor. Ini adalah domain pengetahuan, sikap, dan keterampilan. Therefore, the situation and conditions of supporting teaching and learning activities, the availability of facilities, and other factors must be adjusted to the educational goals to be achieved. The objective of this research is to discover a significant learning theory for teachers and students, so that learning goals may be achieved effectively and efficiently. This study is a